Cytoreductive radiotherapy combined with abiraterone in metastatic castration-resistance prostate cancer: a single center experience - Liu, Yang (Radiat Oncol, 2021)
BACKGROUND: To investigate the potential benefit of cytoreductive radiotherapy (cRT) in metastatic castration-resistant prostate cancer (mCRPC) patients receiving abiraterone. METHODS: From February 2014 to February 2019, 149 mCRPC patients treated with abiraterone were identified. Patients receiving cRT before abiraterone failure (AbiRT group) were matched by one-to-two propensity score to patients without cRT before abiraterone failure (non-AbiRT group). RESULTS: The median follow-up was 23.5 months. Thirty patients (20.1%) were in the AbiRT group, whereas 119 patients (79.9%) were in the non-AbiRT group. The 2-year OS of patients managed by AbiRT and non-AbiRT were 89.5% and 73.5%, respectively (P = 0.0003). On multivariate analysis, only AbiRT (HR 0.17; 95% CI 0.05–0.58; P = 0.004) and prognostic index (HR 2.71; 95% CI 1.37–5.35; P = 0.004) were significant factors. After matching, AbiRT continued to be associated with improved OS (median OS not reached vs. 44.0 months, P = 0.009). Subgroup analysis revealed that patients aged ≤ 65 years (HR 0.09; 95% CI 0.01–0.65; P = 0.018), PSA ≤ 20 ng/mL (HR 0.29; 95% CI 0.09–0.99; P = 0.048), chemotherapy-naïve upon abiraterone treatment (HR 0.20; 95% CI 0.06–0.66; P = 0.008) and in intermediate prognosis groups by COU-AA-301 prognostic index (HR 0.13; 95% CI 0.03–0.57; P = 0.007) had improved OS with AbiRT. CONCLUSIONS: cRT before resistance to abiraterone may improve survival in selected mCRPC patients: age ≤ 65 years old, chemotherapy-naïve, with a relatively low PSA level at the diagnosis of mCRPC and intermediate prognosis.